On the set of extremal functions in certain Kolmogorov-type inequalities - Kofanov, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We determine the sets of all extremal functions in certain Kolmogorov-type and Bohr-Favard-type inequalities.